2017
DOI: 10.1016/j.schres.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Review of thalamocortical resting-state fMRI studies in schizophrenia

Abstract: Brain circuitry underlying cognition, emotion, and perception is abnormal in schizophrenia. There is considerable evidence that the neuropathology of schizophrenia includes the thalamus, a key hub of cortical-subcortical circuitry and an important regulator of cortical activity. However, the thalamus is a heterogeneous structure composed of several nuclei with distinct inputs and cortical connections. Limitations of conventional neuroimaging methods and conflicting findings from post-mortem investigations have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
117
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(138 citation statements)
references
References 92 publications
17
117
2
2
Order By: Relevance
“…In our analysis, the most affected regions and domains include the thalamus of the subcortical domain; BA 38 of the attention domain; the left insula, left BA 44, right BAs 41/42 and the rostral area of left BA 22 of the language domain; and the fusiform gyrus, medioventral, and lateral occipital cortex of the visual domain. The thalamus is known as a major brain structure affected both structurally and functionally in patients with SZ (Cheng et al, 2015; Damaraju et al, 2014; Giraldo-Chica and Woodward, 2017). Disruption in attention associated areas is frequently reported in patients with schizophrenia (Bowie and Harvey, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, the most affected regions and domains include the thalamus of the subcortical domain; BA 38 of the attention domain; the left insula, left BA 44, right BAs 41/42 and the rostral area of left BA 22 of the language domain; and the fusiform gyrus, medioventral, and lateral occipital cortex of the visual domain. The thalamus is known as a major brain structure affected both structurally and functionally in patients with SZ (Cheng et al, 2015; Damaraju et al, 2014; Giraldo-Chica and Woodward, 2017). Disruption in attention associated areas is frequently reported in patients with schizophrenia (Bowie and Harvey, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep spindles are generated from the reticular thalamic nucleus, particularly during NREM sleep, and several previous studies have documented dysconnectivity in the thalamo‐cortical networks in patients with schizophrenia (Giraldo‐Chica & Woodward, ). Reports of clinical correlates of thalamo‐cortical dysconnectivity in schizophrenia have been inconsistent, but a relation to symptom severity has been described (Cheng et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence has suggested that, during liver fibrosis and cirrhosis, the process of angiogenesis is associated with the progress of hepatic fibrogenesis [19]. Interestingly, pathological angiogenesis contributes to HSC activation causing liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%